고효율 방사선 검출 센서를 위한 PbO 박막의 소결효과에 대한 연구 - 정숙희; Sukhee Jung; 김윤석; Yoonsuk Kim; 김영빈; Youngbin Kim; 김민우; Minwoo Kim; 오경민; Kyungmin Oh; 윤민석; Minseok Yun; et al. (Journal of the Korean Society of Radiology, 2009)
본 연구에서는 디지털 엑스레이 검출기의 직접 방식 다결정 lead oxide(PbO)를 이용하여 고효율 방사선 검출 센서를 제작하였다. 나노 크기의 PbO 입자들은 높은 효율을 가지기 위하여 액상법에 의한 합성법을 통하여 제작되었다. 제작된 나노 크기의 PbO 입자를 이용하여 실온에서 200㎛ 두께의 후막을 PIB(particle-in-binder) 방법으로 다양한 온도에서 ITO(Induim Tin Oxide) 유리 위에 도포되었다. 제작된 PbO 후막은 누설전류, 엑스레이 감도, 신호 대 노이즈 비(SNR)을 통해 전기학적 특성이 분석되었다. 이로서 후막의 전기적 특성이 열처리 온도에 따라 많은 영향을 미치는 것을 발견하였고 산소 분위기에서 500℃의 온도로 열처리과정을 거친 후막이 엑스레이 검출 센서로서의 효율이 가장 높다는 결론을 도출할수 있었다. In this study, we made a high efficiency x-ray detecting sensor using the lead oxide(PbO) that are used in direct method of x-ray detector. PbO with nano size particles is produced by sol-gel method for high efficiency. The produced PbO with nano size is deposited on ITO(Induim Tin Oxide) glass in several temperature using the PIB(particle-in-binder) method. The thickness of the deposited PbO is about 200㎛. Through the measurement of dark current, sensitivity and SNR(Signal To Noise Ratio) , an electrical properties of the produced PbO film are analyzed. Therefore, we show that an electrical properties are changed according to a temperature and that the PbO film that was treated at 500℃ in O2 atmosphere is the most high efficiency x-ray detecting sensor.